2012
DOI: 10.1021/cs300103k
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Carbon with SO3H Groups as a Solid Brønsted Acid Catalyst

Abstract: Homogeneous Brønsted acid catalysts such as H2SO4 and HCl are used for the production of industrially important chemicals. However, their use requires significant energy costs for separation, reuse, and treatment of salt wastes. Alternatively, heterogeneous Brønsted acid catalysts are promising candidates that can decrease the environmental impact associated with chemical production. In this review, we highlight amorphous carbon bearing SO3H groups as an insoluble Brønsted acid available for various acid-catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
301
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(310 citation statements)
references
References 66 publications
8
301
0
1
Order By: Relevance
“…These advantages can compensate the problems arising by homogeneous Brönsted acid catalysts in industrial transesterification processes. 37 Interestingly, catalyses promoted by Amberlyst-15 (dry) and -16 (wet) acid resins ( Figure 4) were quite similar to each other and led to a mixture of mono, di and triacetins with a large predominance of diacetin. Aiming to attain total glycerol conversion and the equilibrium selectivity for both resins, the reaction was carried out on Amberlyst-15 (dry) and Amberlyst-16 (wet), under the same conditions showed in Figure 4, except for the glycerol:EtOAc ratio.…”
Section: Resultsmentioning
confidence: 82%
“…These advantages can compensate the problems arising by homogeneous Brönsted acid catalysts in industrial transesterification processes. 37 Interestingly, catalyses promoted by Amberlyst-15 (dry) and -16 (wet) acid resins ( Figure 4) were quite similar to each other and led to a mixture of mono, di and triacetins with a large predominance of diacetin. Aiming to attain total glycerol conversion and the equilibrium selectivity for both resins, the reaction was carried out on Amberlyst-15 (dry) and Amberlyst-16 (wet), under the same conditions showed in Figure 4, except for the glycerol:EtOAc ratio.…”
Section: Resultsmentioning
confidence: 82%
“…A general synthetic approach for the so-called "sugar catalyst" typically consists in the partial carbonization of the carbohydrate substrates through pyrolysis at 200-300 ºC followed by refluxing with sulfuric acid to generate sulfonic functional groups [72][73][74]. The thermally carbonized material typically displays a surface area of less than 5 m 2 /g that is independent from the pyrolysis temperature and sulfonation conditions [74]. The produced carbons were reported to have a sheet-like structure containing 1.2-1.3 nm aromatic domains, structurally similar to graphene [74].…”
Section: Thermal Carbonizationmentioning
confidence: 99%
“…The thermally carbonized material typically displays a surface area of less than 5 m 2 /g that is independent from the pyrolysis temperature and sulfonation conditions [74]. The produced carbons were reported to have a sheet-like structure containing 1.2-1.3 nm aromatic domains, structurally similar to graphene [74].…”
Section: Thermal Carbonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various of solid acid catalysts, such as the sulfonated carbon materials (Toda et al 2005;Nakajima and Hara 2012;Van de Vyver et al 2010;Pang et al 2010;Onda et al 2008;Suganuma et al 2008), ionexchange resins (Rinaldi et al 2008), heteropolyacids (Tian et al 2010) and transition-metal oxide (Takagaki et al 2008;Nakajima et al 2011), etc., have been found active for the hydrolysis of cellulose. In particular, the sulfonated carbon catalysts were widely studied since Hara et al (Toda et al 2005) reported it effective for biodiesel production from vegetable oil.…”
Section: Introductionmentioning
confidence: 99%